Quantifying population harm from indoor air contaminants in dwellings - Morantes Quintana, Giobertti (2024)
Airborne contaminants cause significant harm to populations of people. People spend most of their time in their own homes and so their greatest exposure is likely to occur there. Existing standards that govern Acceptable Indoor Air Quality (IAQ) in residential buildings only consider a few contaminants. Exposure to them is limited using threshold mean concentrations over some period of time, but they do consider the harm they cause to populations of people.